RIGHTS TO FREEDOM OF EXPRESSION OF POLITICAL OPINIONS AS THE FUNDAMENTAL BASIS OF A DEMOCRATIC SOCIETY - BAITALYUK, ZORYANA (Ehrlich's Journal, 2024)
Abstract. It is determined that the freedom of expression of political views is a legally guaranteed opportunity to freely collect and accumulate information about the socio-historical conditions of the development of a specific political party, political process, society and state and, on this basis, to form one's own political position as a system of political views. It was found that the content of the freedom of expression of political views includes: the right of everyone to freely define their own political position; the right not to disclose one's political position to other persons; the right to protection against the attribution of a certain position on the basis of one's previous statements; the right to freely publicize and disseminate one's political beliefs through various means of expression. The structure of this legal phenomenon includes: direct implementation of this right; activities of competent bodies and officials to ensure the realization of this right; dialogue between people and the state in the person of competent authorized bodies regarding the achievement of positive changes in certain political processes or phenomena, which is manifested in people's expression of their political views, demonstration of acceptance or non-acceptance of ongoing political processes. It was concluded that the freedom of expression of political views in combination with other fundamental rights and freedoms allows humanity and each individual person to move in the right general democratic direction; it is the basis of democracy in the modern world and an indicator of the civilized development of the state and civil society.